Clinical Presentation and Treatment Outcomes of Children and Adolescents With Pheochromocytoma and Paraganglioma in a Single Center in Korea - Park, Hyojung; Kim, Min-Sun; Lee, Jiwon; Kim, Jung-Han; Jeong, Byong Chang; Lee, Sanghoon; Lee, Suk-Koo; Cho, Sung Yoon; Jin, Dong-Kyu (Frontiers in Endocrinology, 2021)
Purpose: Pheochromocytoma (PCC) and paraganglioma (PGL) (PPGL) are rare neuroendocrine tumors, and data on managing these conditions in children and adolescents are lacking. The objective of this study was to demonstrate the clinical presentation and treatment outcomes in children and adolescents with PPGL in a single tertiary care center in Korea. Methods: This retrospective study included 23 patients diagnosed with PCC (n = 14) and PGL (n = 9) before the age of 21 at Samsung Medical Center (from June 1994 to June 2019). We describe age, gender, family history, clinical characteristics, laboratory findings, pathologic findings, therapeutic approaches, and treatment outcomes. Results: Of the 23 patients, 14 had PCC and nine had PGL. The median age at diagnosis was 16.8 years (range, 6.8–20.8 years). The common presenting symptoms were hypertension (n = 10), headache (n = 9), palpitation (n = 4), and sweating (n = 4). The plasma or 24-hour urine catecholamine and/or metabolite concentrations were markedly elevated in 22 patients with PPGL, but were normal in one patient with carotid body PGL. All tumors were visualized on computed tomography. Genetic tests were performed in 15 patients, and seven patients showed mutations in RET (n = 3), SDHB (n = 3), and VHL (n = 1). All patients underwent surgery, and complete excision was performed successfully. Three patients with metastasis underwent postoperative adjuvant therapy. Conclusion: This study suggests that pediatric PPGL tends to be extra-adrenal and bilateral and shows a higher potential for genetic mutations. Considering the hereditary predisposition of pediatric PPGL, genetic screening tests are strongly recommended, and lifelong follow-up is needed to detect recurrence and metastasis. Further research with a larger sample size and routine genetic screening is needed to better understand the genetic conditions and long-term prognosis of PPGL.